2008
DOI: 10.1097/scs.0b013e31848432e4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Preoperative Local Ropivacaine Infiltration on Postoperative Pain Scores in Infants and Small Children Undergoing Elective Cleft Palate Repair

Abstract: Previous data have shown that preoperative analgesia may reduce postoperative analgesic demands. The aim of the current study was to determine if preincisional ropivacaine infiltration may reduce postoperative oral pain in infants and small children undergoing elective cleft palate patients.Twenty nonsyndromic cleft palate patients were randomly divided into 2 groups. Injection with ropivacaine hydrochloride, at dose of 0.2 mg/kg, was performed by submucous infiltration of the proposed incisional site groups o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Therefore, it seems advisable to use ropivacaine as a supplemental IANB after surgical removal of impacted lower third molars regardless the type of local anesthetic used to induce the IANB for painless surgery. Furthermore, the data reported by Coban et al [30] showed that even preemptive analgesia of ropivacaine (0.2 mg/kg), injected by maxillary infiltration in primary cleft palate repair, may reduce early postoperative pain and rescue analgesic therapy. However, the possibility of nerve injury with a repeat supplemental mandibular injection has to be discussed.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, it seems advisable to use ropivacaine as a supplemental IANB after surgical removal of impacted lower third molars regardless the type of local anesthetic used to induce the IANB for painless surgery. Furthermore, the data reported by Coban et al [30] showed that even preemptive analgesia of ropivacaine (0.2 mg/kg), injected by maxillary infiltration in primary cleft palate repair, may reduce early postoperative pain and rescue analgesic therapy. However, the possibility of nerve injury with a repeat supplemental mandibular injection has to be discussed.…”
Section: Discussionmentioning
confidence: 95%
“…The literature is replete with the use of adjunct medications and regional injection techniques in an attempt to decrease overall narcotic use. [2][3][4][5][6] Comparisons also extend to the type of narcotic used. 7 Our experience with iliac crest harvesting analgesia led us to believe that by soaking a hemostatic pledget with bupivacaine, we could improve long-term analgesia, earlier return of oral intake, and earlier discharge from the hospital.…”
Section: Discussionmentioning
confidence: 98%
“…Most published articles have showed that preoperative analgesia could decrease postoperative analgesic demands 14,15 ; however, the aim of this study was to prospectively evaluate preoperative and perioperative analgesic effects of peripheral nerve block for TN. There are 2 reasons: first, for the patients scheduled to undergo surgery, it is difficult to control severe pain using medical treatment, so the patients might experience serious pain attacks before and during operation; second, these patients are vulnerable to pain-related comorbidities, such as anxiety, depression, and sleep disturbance, 6 which might badly affect operation.…”
Section: Discussionmentioning
confidence: 99%
“…14 Another research showed that preoperative local administration of ropivacaine decreased postoperative pain scores in infants and small children undergoing elective cleft palate repair. 15 Continuous 16 and single administration 17 of local analgesic have been used to treat TN. A single local anesthetic block sometimes relieves pain for several weeks in patients with painful peripheral neuropathy.…”
Section: Discussionmentioning
confidence: 99%